1995
DOI: 10.1021/bi00025a007
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Ternary Complex Formation by Histone H1, DNA, and Liposomes

Abstract: Using three different donor-acceptor pairs for resonance energy transfer, interactions in systems composed of histone H1, liposomes, and DNA were investigated. While weak attachment of H1 to phosphatidylcholine (PC) liposomes was observed, the inclusion of phosphatidylserine (PS), phosphatidylglycerol (PG), or phosphatidic acid (PA) strongly enhanced the membrane association of H1, the extent of binding increasing with the content of the acidic lipid. Increasing the content of the negatively charged lipid also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 62 publications
3
42
0
Order By: Relevance
“…Complexes composed exclusively of neutral (zwitterionic) lipids offer an alternative to CLs, in that they exhibit lower inherent cytotoxicity, 17,18 much longer circulation lifetimes, and very different clearance profiles. 19 Within this frame, some of the present authors have recently studied ternary complexes formed by the self-assembled association of neutral liposomes (L's), DNA, and bivalent metal cations in water solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Complexes composed exclusively of neutral (zwitterionic) lipids offer an alternative to CLs, in that they exhibit lower inherent cytotoxicity, 17,18 much longer circulation lifetimes, and very different clearance profiles. 19 Within this frame, some of the present authors have recently studied ternary complexes formed by the self-assembled association of neutral liposomes (L's), DNA, and bivalent metal cations in water solutions.…”
Section: Introductionmentioning
confidence: 99%
“…In animals, lipids in the PI pathway have been shown to interact with DNA and may regulate DNA replication (reviewed in Koiv et al, 1995; Kuvichkin, 2002). Studies have shown PtdInsP to decrease α, δ, and ε DNA polymerase activity (Shoji-Kawaguchi et al, 1995).…”
Section: The Pi Pathway and Dna Synthesismentioning
confidence: 99%
“…In particular, the presence of histones and other positively charged proteins in chromatin raises the possibility that these proteins interact with negatively charged lipids in the nuclear membrane. In fact, several authors (10)(11)(12) have studied the interaction of histones with phosphatidylserine and other negatively charged lipids that exist in very minor amounts in the NE. In a previous study (13), we found that a variety of histone and histone combinations (H1, H2AH2B, H3H4, and octamers) caused a dose-dependent aggregation of phospholipid vesicles composed mainly of phosphatidylcholine (PC) to which 5-20 mol % phosphoinositides was added.…”
Section: Introductionmentioning
confidence: 99%